Sentinel node involvement with or without completion axillary lymph node dissection: treatment and pathologic results of randomized SERC trial - Gilles Houvenaeghel; Monique Cohen; Pédro Raro; Jérémy De Troyer; Pierre Gimbergues; Christine Tunon de Lara; Vivien Ceccato; Véronique Vaini-Cowen; Christelle Faure-Virelizier; Frédéric Marchal; Tristan Gauthier; Eva Jouve; et al. (npj Breast Cancer, 2021)
Abstract Based on results of clinical trials, completion ALND (cALND) is frequently not performed for patients with breast conservation therapy and one or two involved sentinel nodes (SN) by micro- or macro-metastases. However, there were limitations despite a conclusion of non-inferiority for cALND omission. No trial had included patients with SN macro-metastases and total mastectomy or with >2 SN macro-metastases. The aim of the study was too analyze treatment delivered and pathologic results of patients included in SERC trial. SERC trial is a multicenter randomized non-inferiority phase-3 trial comparing no cALND with cALND in cT0-1-2, cN0 patients with SN ITC (isolated tumor cells) or micro-metastases or macro-metastases, mastectomy or breast conservative surgery. We randomized 1855 patients, 929 to receive cALND and 926 SLNB alone. No significant differences in patient’s and tumor characteristics, type of surgery, and adjuvant chemotherapy (AC) were observed between the two arms. Rates of involved SN nodes by ITC, micro-metastases, and macro-metastases were 5.91%, 28.12%, and 65.97%, respectively, without significant difference between two arms for all criteria. In multivariate analysis, two factors were associated with higher positive non-SN rate: no AC versus AC administered after ALND (OR = 3.32, p < 0.0001) and >2 involved SN versus ≤2 (OR = 3.45, p = 0.0258). Crude rates of positive NSN were 17.62% (74/420) and 26.45% (73/276) for patient’s eligible and non-eligible to ACOSOG-Z0011 trial. No significant differences in patient’s and tumor characteristics and treatment delivered were observed between the two arms. Higher positive-NSN rate was observed for patients with AC performed after ALND (17.65% for SN micro-metastases, 35.22% for SN macro-metastases) in comparison with AC administered before ALND.